Reversible Data Hiding and Reversible Authentication Watermarking for Binary Images - Pamboukian, Sergio Vicente D.; Kim, Hae Yong (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2006: Anais do VI Simpósio Brasileiro de Segurança da Informação e de Sistemas ComputacionaisDO - 10.5753/sbseg.2006.20942, 2006)
Data hiding is a technique used to embed a sequence of bits in a host image with small visual deterioration and the means to extract it afterwards. Reversible data hiding allows, in addition, recovering the original coverimage exactly. Several reversible data hiding techniques have been developed but none of them seems to be appropriate for binary images. This paper proposes a reversible data hiding for binary images. The proposed technique selects a set of low-visibility pixels and uses the Golomb code to compress the predictions of these pixels. This compressed data and the net payload data are embedded into the image. Images watermarked by the proposed technique have excellent visual quality, because only low-visibility pixels are flipped. Then, we use the proposed data hiding to reversibly authenticate binary images and documents. This technique has many potential practical uses, including lossless authenticated FAX transmission and reversible content protection of binary document databases.